Resilience Assessment Tool 43 (RAT-43) - Amalia, Madihie; Salmah, Mohamad Yusoff; Jamayah, Saili; Siti Norazilah, Mohd Said (Human Resilience and Potential Centre, Faculty of Cognitive Sciences and Human Development, Universiti Malaysia Sarawak, 2025)
The Resilience Assessment Tool-43 (RAT-43) is designed to assess resilience levels in individuals aged 10 years and above. Developed by Amalia Madihie, Salmah Mohamad Yusoff, Jamayah Saili, and Siti Norazilah Mohd Said from the Counselling Programme, Faculty of Cognitive Sciences and Human Development, Universiti Malaysia Sarawak (UNIMAS), Malaysia, the instrument is grounded in the Resilience Framework proposed by Hart et al. (2007).